Transdermal carbamate poisoning – a case of misuse - Rajbanshi, Lalit Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Acute pesticide poisoning is a common mode of intentional self harm. Oral ingestion is the usual mode of poisoning. However, inhalation, accidental or occupational transdermal exposure leading to acute or chronic poisoning can be the other route of poisoning. It has been seen that the purpose of poising is suicidal intensity in most of the cases. We report an unusual case where the victim had acute pesticide poisoning through transdermal route that was intended for non suicidal purpose. The patient was managed successfully with immediate decontamination and adequate antidote.